THE EFFECT OF AMMONIA VAPOR CONCENTRATION AND TENSILE STRESS IN SCC (STRESS CORROSION CRACKING) RESISTANCE OF UNS C44300 TUBE MATERIAL - Rahma Giffari, Aisyah
UNS C44300 material is one of the materials that is widely used in the tube heat exchanger because it has good mechanical properties and corrosion resistance. But, this material is sensitive to SCC (Stress Corrosion Cracking) in an ammonia environment. In heat exchanger applications, the amount of dissolved oxygen is limited by adding an oxygen scavenger to reduce the risk of corrosion. However, some types of oxygen scavenger will produce ammonia when used, so that it can trigger SCC. In this research, UNS C44300 material testing based on ASTM G38 using the vapor method in ammonia vapor. This research used various ammonia concentrations of 1, 1,5, and 2 Molar. Also, variations in tensile stress are used in the material of 10, 30, 50, and 80% yield strength. These variations are used to determine the effect of increasing concentration and tensile stress on the crack length and weight loss of the material. The results showed, that the crack length and weight loss were increase with the increase ammonia vapor concentration and tensile stress. The crack initiation does not occur when the tensile stress is less than 20% yield strength.